Implementation DeLone & McLean IS Success Model for Research and Community Service Management Information System Evaluation - Awang Hendrianto Pratomo; Riza Prapascatama Agusdin; Sylvert Prian Tahalea; Nur Heri Cahyana (Universitas Pembangunan Nasional Veteran Yogayakarta, 2021)
SRIKANDI is an information system managed by LPPM that manages research and lecturer service within the UPN